If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -3 + z = 23 Reorder the terms: -3 + 3z + z = 23 Combine like terms: 3z + z = 4z -3 + 4z = 23 Solving -3 + 4z = 23 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 4z = 23 + 3 Combine like terms: -3 + 3 = 0 0 + 4z = 23 + 3 4z = 23 + 3 Combine like terms: 23 + 3 = 26 4z = 26 Divide each side by '4'. z = 6.5 Simplifying z = 6.5
| -23-11-(-7)+(-25)= | | 6x-11y=8 | | 15y=-4+5x | | t+12(3t-t^2)= | | -3+6.2=-5.8 | | 1.2x-1=2(1.6x+1.5) | | 83x=-33 | | 50x^2-2= | | 81t-64t=0 | | .3x-x=-16 | | .3x-x=16 | | f(s)=s^2(s^2+2) | | 3x-(6-2x)=39 | | 3z-6=z+4 | | .26d=.104 | | 7.46=2*3.14*r | | x-1.34=9 | | 7(z-2)=3(z-1) | | 0.56+0.46t=4.36t-1.00 | | -1.7s=2.21 | | 22x-17=2x+8 | | 8v-42=3(v-9) | | -3.4s=3.74 | | y+4(2)=6 | | 81=n-57 | | 4y-13z+-10y+17z= | | -12=6x-8x-6 | | 2(5-4x)=(10+7x) | | -12=6x-8x-12 | | -16x^2+96x+2=0 | | -x+7=-x-7 | | 172=7x+x |